Dimensional Synthesis Design of a Walking Aided Training Robot - Qin Tao (Jixie chuandong)
In order to help patients with lower extremity dysfunction complete walking rehabilitation training,a plantar-driven walking aided training robot mechanism is designed. According to the change laws of ankle and knee joint posture during normal walking,the dimensional synthesis optimization of ankle joint attitude restraining mechanism and aided knee flexion mechanism is carried out to determine the optimal size parameters of the mechanism. According to the rotation laws and range of the plantar,the trajectory of restraint guide rail ζof ankle joint attitude restraining mechanism is comprehensively determined,and the effects of confined guide way inclination angle and pedal length on the angle range of ankle joint are analyzed. The aided knee flexion mechanism is designed to help the affected limbs flexibly in the knee during walking training,and the influence of mechanism dimension on the aided knee flexion is analyzed and determined. The simulation model of the mechanism is established by using the Matlab toolbox,and the rationality of dimensional synthesis optimization and the feasibility of robot mechanism design is verified by the results of simulation analysis.